The genome of Nautilus pompilius illuminates eye evolution and biomineralization - Zhang, Yang; Mao, Fan; Mu, Huawei; Huang, Minwei; Bao, Yongbo; Wang, Lili; Wong, Nai-Kei; Xiao, Shu; Dai, He; Xiang, Zhiming; Ma, Mingli; Xiong, Yuanyan; et al. (Nature ecology & evolution, 2021)
Nautilus is the sole surviving externally shelled cephalopod from the Palaeozoic. It is unique within cephalopod genealogy and critical to understanding the evolutionary novelties of cephalopods. Here, we present a complete Nautilus pompilius genome as a fundamental genomic reference on cephalopod innovations, such as the pinhole eye and biomineralization. Nautilus shows a compact, minimalist genome with few encoding genes and slow evolutionary rates in both non-coding and coding regions among known cephalopods. Importantly, multiple genomic innovations including gene losses, independent contraction and expansion of specific gene families and their associated regulatory networks likely moulded the evolution of the nautilus pinhole eye. The conserved molluscan biomineralization toolkit and lineage-specific repetitive low-complexity domains are essential to the construction of the nautilus shell. The nautilus genome constitutes a valuable resource for reconstructing the evolutionary scenarios and genomic innovations that shape the extant cephalopods. Nautilus, the sole surviving externally shelled cephalopod from the Palaeozoic, holds an important phylogenetic position to understand the evolution of cephalopods. A complete genome of Nautilus pompilius sheds light on the evolution of the pinhole eye and biomineralization.